COMPETITIVENESS OF THE EU ECONOMIES AND DEVELOPMENT OF CLUSTERS - Figiel, Szczepan; Kuberska, Dominika (European Scientific Journal, ESJ, 2013)
The role of business clusters in building competitive advantage of national economies is a subject of numerous discussions. It is rather quite commonly agreed that well developed business clusters are supposed to be drivers of innovation and competitiveness of economy in multifold dimensions. In the article a hypothesis, which states that occurrence of numerous and strong clusters in a country is positively related to competitiveness of its economy is being tested. Using a dataset on cluster mapping in Europe from the European Cluster Observatory and results of the country competitiveness rankings published by the World Economic Forum in the Global Competitiveness Reports as well as data on the levels of Gross Domestic Product (GDP) from World Bank we have looked for a relationship between occurrence and relative strength of clusters in the EU-27 countries and the measures of competiveness such as the competitive potential and productivity of the EU national economies. It appeared from the analysis that those countries differ in terms of both occurrence and relative strength of business clusters as well as levels measures of their competitiveness such GDP per capita and the competitive potential. Nevertheless, statistical evidence for relationships between variables under consideration was not found what leads to some suggestions regarding cluster mapping methodology and further studies in this area, which could result in formulating useful recommendations for public policies aimed at development of clusters.